On modern poetry - Mazzoni, Guido 1967-; Hanafi, Zakiya 1959- (Cambridge, Massachusetts The Belknap Press of Harvard University Press, 2022)
"Guido Mazzoni tells the story of poetry's revolution in the modern age. The chief transformation was the rise of the lyric as it is now conceived: a genre in which a first-person speaker talks about itself. Mazzoni argues that modern poetry embodies the age of the individual and has wrought profound changes in the expectations of readers"--Provided by publisher.
First edition originally published in Italian as Sulla poesia moderna (Bologna : Società editrice il Mulino, 2005) --Title page verso.
Includes index.
Keywords: Italian poetry -- 19th century -- History and criticism; Italian poetry -- 20th century -- History and criticism; Poetry, Modern -- 19th century -- History and criticism; Poetry, Modern -- 20th century -- History and criticism; Electronic books